Liquid rubber pre-composite nanosheet filler masterbatch and use in tires

CN122898047APending Publication Date: 2026-10-13ZHONGCE RUBBER GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611167054.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

若液体橡胶与纳米片层填料分别加入密炼体系,液体橡胶难以在纳米片层填料进入胶料前对其充分润湿和包覆,仍不能有效防止片层填料在投料及混炼过程中发生团聚

Benefits of technology

[0028]本发明通过在低氧或惰性气氛下对纳米片层填料与液体橡胶进行高剪切分散、球磨分散或二者的组合处理,使纳米片层填料在进入胎面胶之前即被液体橡胶充分润湿和包覆,并将其团聚体尺寸控制在适宜范围内,从而降低片层之间的直接接触和重新堆叠倾向;所得预复合母料在后续混炼过程中能够以液体橡胶为载体较均匀地进入目标橡胶相区,减少纳米片层填料与白炭黑之间的无效聚集,并降低对既有白炭黑—硅烷补强网络的不利扰动。进一步结合分阶段混炼及母料加入时点和排胶温度的控制,可减少纳米片层填料在高温、高剪切条件下的二次团聚,使胎面胶获得较低的Payne指数、较高的0℃损耗因子和较低的60℃损耗因子,在保持适宜加工黏度的同时,提高湿地制动性能,降低滚动阻力,并改善耐磨性能、裂口扩展阻力和耐久性能。与纳米片层填料粉体直接加入或者液体橡胶与纳米片层填料分别加入的方式相比,本发明能够获得更稳定的填料分散状态和更优的多性能综合平衡,且所采用的原材料和混炼工艺能够与现有轮胎生产设备相适配,具有良好的工艺可实施性和工业应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898047A_ABST
    Figure CN122898047A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of rubber composite material and tire tread rubber preparation, and particularly relates to a liquid rubber pre-composite nano-slabbed filler masterbatch and application thereof in tires. The masterbatch comprises liquid rubber and nano-slabbed filler; under the condition that the oxygen content is not higher than 8 vol.%, the nano-slabbed filler is wetted and coated by the liquid rubber through ball milling and / or high shear treatment. The masterbatch is added in the second stage of the high-white carbon black tread rubber, and a vulcanization system is added at the end of the mixing. The method can reduce the agglomeration and secondary aggregation of the slabbed filler, reduce the Payne effect, and improve the comprehensive balance of the wet braking, rolling resistance, wear resistance and crack propagation resistance of the tire tread.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rubber composite materials and tire tread preparation technology, specifically relating to a liquid rubber precomposite nanosheet filler masterbatch and its application in tires. Background Technology

[0002] As the automotive industry moves towards higher speeds, electrification, and lower energy consumption, high-performance passenger car tires and new energy vehicle tires place higher demands on the wet grip, rolling resistance, abrasion resistance, crack resistance, and processing stability of tread compounds. Silica combined with silane coupling agents can, to some extent, balance wet grip and rolling resistance, and is therefore widely used in tire tread compounds. However, when the amount of silica used is high, a strong filler network easily forms between the silica particles, leading to increased compound viscosity, difficulty in dispersion, and increased dynamic hysteresis loss, making it difficult to simultaneously achieve wet braking, low rolling resistance, abrasion resistance, and crack propagation resistance.

[0003] Nanosheet fillers such as graphene, reduced graphene oxide, graphene nanosheets, and layered silicates possess large specific surface areas and aspect ratios, and can form interfacial reinforcement structures or crack deflection paths in rubber matrices, thus showing potential to improve the reinforcement, thermal conductivity, wear resistance, and crack resistance of rubber. However, nanosheet fillers exhibit strong interlayer interactions, and when directly added as powder to an internal mixer, they are prone to stacking and agglomeration. Especially in high-precision silica tread rubbers, nanosheet fillers can compete with silica for the rubber matrix and interfacial modifiers, making the filler network more complex and potentially leading to problems such as increased rubber viscosity, enhanced Payne effect, formation of local weak phases, and fluctuations in dynamic properties.

[0004] Chinese invention patent application publication number CN105482201A discloses a high-performance tire containing graphene oxide. The method involves dispersing graphene oxide in water and mixing it with natural rubber latex. After flocculation, washing, and drying, a masterbatch of graphene oxide and natural rubber is obtained. This masterbatch is then used in a tread compound containing natural rubber, butadiene rubber, styrene-butadiene rubber, highly dispersed silica, and a silane coupling agent to improve the dispersion of graphene oxide in the rubber and the physical and mechanical properties of the tread compound. This technology employs a wet latex compounding process, involving steps such as aqueous dispersion, flocculation, washing, and drying, resulting in a relatively long process flow. The masterbatch carrier is solid natural rubber, and the method does not address the pre-wetting and coating of nanosheet fillers with low-molecular-weight liquid rubber, nor does it propose corresponding measures for the synergistic regulation between the nanosheet fillers and the silica-silane network in the high-silica system.

[0005] Chinese invention patent application publication number CN116669863A discloses a rubber composition containing graphene and liquid rubber. This composition reduces the size of reduced graphene oxide and improves its dispersibility by grinding reduced graphene oxide in liquid rubber without the use of solvents. The document also describes a technique for grinding reduced graphene oxide and liquid rubber using a ball mill under nitrogen conditions, and then adding the resulting ground material to an uncured rubber elastomer. This technology can reduce the processing difficulty of reduced graphene oxide powder and, to some extent, inhibit layer recombination. However, it mainly focuses on the grinding of reduced graphene oxide and liquid rubber and their dispersion in general rubber compositions. It has not yet solved the problem of complex filler networks when high amounts of silica, silane coupling agents, and multiple base rubbers coexist. Furthermore, it does not propose a technical solution for synergistically controlling the masterbatch addition stage and the mixing temperature at each stage based on the masterbatch agglomerate particle size and the target rubber phase region.

[0006] Furthermore, liquid rubber is typically added directly to rubber compositions as a plasticizer, processing aid, or reactive plasticizer. If liquid rubber and nanosheet fillers are added separately to the mixing system, the liquid rubber cannot adequately wet and coat the nanosheet fillers before they enter the rubber compound, thus failing to effectively prevent agglomeration of the nanosheet fillers during feeding and mixing. Even if a mixture of nanosheet fillers and liquid rubber is prepared in advance, secondary agglomeration may occur due to insufficient coating, decreased wetting ability, or high-temperature, high-shear conditions if the agglomerate size, liquid rubber molecular weight, filler-to-liquid rubber ratio, and improper control during the addition stage.

[0007] Therefore, it is still necessary to provide a nanosheet filler masterbatch technology suitable for high silica tire tread systems. This technology involves pre-wetting, pre-coating, and controlled dispersion of the nanosheet filler with liquid rubber, and then allowing the resulting masterbatch to enter the rubber matrix during a suitable mixing stage. This reduces the agglomeration and secondary aggregation of the nanosheet filler, regulates the interaction between the nanosheet filler and the silica-silane reinforcing network, and thus improves the overall balance of tire tread rubber in terms of wet braking, rolling resistance, wear resistance, and crack propagation resistance. Summary of the Invention

[0008] The purpose of this invention is to provide a liquid rubber pre-composite nanosheet filler masterbatch, its preparation method, and its application in high-precision carbon black tire tread rubber compositions. The masterbatch is introduced into the high-precision carbon black tread system by pre-wetting, pre-coating, and controlled dispersion of the nanosheet filler using liquid rubber, combined with a staged mixing method. This reduces the agglomeration and secondary aggregation of the nanosheet filler, improves its dispersion in the rubber matrix, and solves the problems of easily disturbing the silica-silane reinforcing network and the difficulty in simultaneously achieving good wet braking, rolling resistance, wear resistance, and crack resistance when nanosheet fillers are directly added.

[0009] Firstly, in order to achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0010] A method for preparing a high-white carbon black tire tread rubber composition includes the following steps:

[0011] S1. In an atmosphere with an oxygen content not exceeding 8 vol.%, reduced graphene oxide and liquid diene rubber with a number average molecular weight of 1500 to 10000 are premixed at a mass ratio of 20:80 to 25:75, and then ball-milled and dispersed and high-shear dispersed in sequence to obtain a liquid rubber precomposite nanosheet filler masterbatch with a median particle size D50 of reduced graphene oxide agglomerates not exceeding 10 μm.

[0012] S2. Based on 100 parts by mass of solid rubber component, a portion of solid rubber component, 50-70% of the total amount of silica and 40-70% of the total amount of silane coupling agent are subjected to a first stage of mastering, and the liquid rubber pre-composite nanosheet filler masterbatch is not added in the first stage of mastering to obtain the first masterbatch.

[0013] S3. The first masterbatch, the remaining solid rubber component, the remaining silica, the remaining silane coupling agent, and the liquid rubber precomposite nanosheet filler masterbatch are subjected to a second stage of masterbatch mixing, so that the amount of the masterbatch added, converted to reduced graphene oxide, is 0.5 to 2.0 parts by mass, and the amount of the masterbatch added, converted to liquid diene rubber, is 3 to 8 parts by mass. The discharge temperature of the second stage masterbatch mixing is 130 to 165°C.

[0014] S4. The rubber compound obtained from the second stage masterbatch is subjected to final refining with sulfur and accelerator. During the final refining process, the liquid rubber pre-composite nanosheet filler masterbatch is not added again, and the final refining discharge temperature is not higher than 110°C, to obtain the high-white carbon black tire tread rubber composition.

[0015] The amount of silica added in the high silica tire tread rubber composition is 80-160 parts by weight, and the liquid rubber pre-composite nanosheet filler masterbatch is added only in the second stage masterbatch.

[0016] Preferably, the liquid diene rubber is selected from one or more of liquid polybutadiene rubber, liquid styrene-butadiene rubber, carboxylated liquid polybutadiene rubber, and epoxidized liquid polybutadiene rubber;

[0017] Preferably, the liquid diene rubber is liquid polybutadiene rubber or liquid styrene-butadiene rubber with a number average molecular weight of 3000-5000.

[0018] Preferably, in step S1, the ball milling dispersion time is 10–300 min; the high shear dispersion temperature is 20–90 °C; and the high shear dispersion time is 5–120 min; nitrogen is used to replace the air in the ball milling container before ball milling dispersion.

[0019] Preferably, the mass ratio of the reduced graphene oxide to the liquid polybutadiene rubber is 20:80, the number average molecular weight of the liquid polybutadiene rubber is 3000-4000, and the median particle size D50 of the reduced graphene oxide agglomerates in the resulting liquid rubber precomposite nanosheet filler masterbatch is not higher than 8 μm.

[0020] Preferably, an interface stabilizer is added during the high-shear dispersion process in step S1. The interface stabilizer is selected from one or more of silane coupling agents, titanate coupling agents, zirconate coupling agents, maleic anhydride grafted oligomers, rosin esters, and terpene phenol resins. The amount of the interface stabilizer added is 0.1 to 10% of the total mass of the liquid rubber precomposite nanosheet filler masterbatch.

[0021] Preferably, based on 100 parts by weight of solid rubber components, the high-silica tire tread rubber composition comprises: 30-70 parts by weight of solution-polymerized styrene-butadiene rubber, 5-40 parts by weight of polybutadiene rubber, 10-50 parts by weight of natural rubber and / or isoprene rubber, 80-160 parts by weight of silica, 0-20 parts by weight of carbon black, and 4-15 parts by weight of silane coupling agent, and the total amount of the solid rubber components is 100 parts by weight;

[0022] Preferably, based on 100 parts by weight of solid rubber components, the high-silica tire tread rubber composition comprises 55 parts by weight of solution-polymerized styrene-butadiene rubber, 20 parts by weight of polybutadiene rubber, 25 parts by weight of natural rubber, 125 parts by weight of silica, 5 parts by weight of carbon black, 10 parts by weight of silane coupling agent, 8 parts by weight of TDAE oil, 2.5 parts by weight of zinc oxide, 1.8 parts by weight of stearic acid, 1.8 parts by weight of antioxidant, 1.2 parts by weight of protective wax, 1.7 parts by weight of sulfur, 1.6 parts by weight of accelerator CZ, and 2.0 parts by weight of accelerator DPG; the amount of masterbatch added, converted to reduced graphene oxide, is 1.5 parts by weight, and the amount added, converted to liquid polybutadiene rubber, is 6 parts by weight.

[0023] Secondly, the present invention also provides a liquid rubber pre-composite nanosheet filler masterbatch for use in high-white carbon black tire tread rubber compositions. The masterbatch comprises nanosheet filler and liquid diene rubber, wherein the mass ratio of the nanosheet filler to the liquid diene rubber is 20:80 to 25:75; the number average molecular weight of the liquid diene rubber is 1500 to 10000; the nanosheet filler is pre-dispersed in the liquid diene rubber, and the median particle size D50 of the nanosheet filler agglomerates in the masterbatch is not higher than 10 μm; the nanosheet filler is selected from one or more of reduced graphene oxide, graphene nanosheets, and organically modified layered silicates.

[0024] Preferably, the nanosheet filler is reduced graphene oxide, the liquid diene rubber is liquid polybutadiene rubber with a number average molecular weight of 3000-4000, the mass ratio of reduced graphene oxide to liquid polybutadiene rubber is 20:80, and the median particle size D50 of the reduced graphene oxide agglomerates is not higher than 8 μm.

[0025] Thirdly, the present invention also provides a high-silica tire tread rubber composition, based on 100 parts by weight of solid rubber components, comprising: 30-70 parts by weight of solution-polymerized styrene-butadiene rubber, 5-40 parts by weight of polybutadiene rubber, 10-50 parts by weight of natural rubber and / or isoprene rubber, 80-160 parts by weight of silica, 0-20 parts by weight of carbon black, 4-15 parts by weight of silane coupling agent, and the liquid rubber pre-composite nanosheet filler masterbatch; the total amount of the solid rubber components... The amount is 100 parts by mass, and the amount of the masterbatch added is 0.5 to 2.0 parts by mass when converted to nanosheet filler, and 3 to 8 parts by mass when converted to liquid diene rubber; the high-white carbon black tire tread rubber composition, under the conditions of a test frequency of 10 Hz and a dynamic strain of 0.5%, has a loss factor tanδ of not less than 0.250 at 0℃, a loss factor tanδ of not more than 0.093 at 60℃, and its ML(1+4) Mooney viscosity at 100℃ is not more than 73.

[0026] Fourthly, the present invention also provides a tire, the tread of which comprises at least the aforementioned high-white carbon black tire tread rubber composition.

[0027] Fifthly, the present invention also provides the application of the liquid rubber pre-composite nanosheet filler masterbatch in the preparation of high silica tire tread rubber composition, characterized in that a portion of the solid rubber component and a portion of silica are first subjected to a first-stage mastering process, and then the liquid rubber pre-composite nanosheet filler masterbatch is subjected to a second-stage mastering process with the rubber compound obtained from the first-stage mastering process, the remaining silica and the remaining silane coupling agent, and the liquid rubber pre-composite nanosheet filler masterbatch is not added in the first-stage mastering process and the final process.

[0028] This invention utilizes high-shear dispersion, ball milling dispersion, or a combination of both of the nanosheet filler and liquid rubber under low-oxygen or inert atmospheres. This ensures that the nanosheet filler is fully wetted and coated by the liquid rubber before entering the tread compound, and controls its agglomerate size within a suitable range, thereby reducing direct contact and re-stacking tendency between the sheets. The resulting pre-composite masterbatch can enter the target rubber phase region more uniformly during subsequent mixing, using the liquid rubber as a carrier, reducing ineffective aggregation between the nanosheet filler and silica, and minimizing adverse disturbances to the existing silica-silane reinforcing network. Furthermore, by combining staged mixing and controlling the timing of masterbatch addition and discharge temperature, secondary agglomeration of the nanosheet filler under high-temperature, high-shear conditions can be reduced. This results in a tread compound with a lower Payne index, a higher 0°C loss factor, and a lower 60°C loss factor. While maintaining suitable processing viscosity, it improves wet braking performance, reduces rolling resistance, and enhances abrasion resistance, crack propagation resistance, and durability. Compared with the direct addition of nanosheet filler powder or the separate addition of liquid rubber and nanosheet filler, the present invention can achieve a more stable filler dispersion state and a better comprehensive balance of multiple properties. Moreover, the raw materials and mixing process used can be adapted to existing tire production equipment, and have good process feasibility and industrial application value. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the process flow of the present invention.

[0030] Figure 2 This is a schematic diagram of the staged mixing process of the liquid rubber precomposite nanosheet filler masterbatch of the present invention in high-white carbon black tread rubber.

[0031] Figure 3 This is a comparison chart of the Payne index and rolling resistance index for Comparative Examples 1, 2, and 5.

[0032] Figure 4 The graph shows the relationship between the median particle size D50 of the nanosheet filler agglomerates and the overall balance index in the examples and comparative examples.

[0033] Figure 5 The radar chart shows the comprehensive performance of Example 5 and Comparative Example 1 in terms of wet braking index, rolling resistance index, wear mileage index, crack propagation resistance index, extrusion appearance score, and durability index. Detailed Implementation

[0034] The present invention will be further described below with reference to the accompanying drawings, embodiments, and comparative examples. It should be understood that the embodiments described are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make conventional adjustments to the types of raw materials, equipment specifications, and process parameters without departing from the concept of the present invention.

[0035] Unless otherwise specified, "parts" in this embodiment refers to parts by mass, and "phr" refers to the number of parts by mass based on 100 parts by mass of the total mass of the solid base rubber in the rubber composition; "liquid rubber" is not included in the 100 parts by mass of the solid base rubber. "Nanosheet filler agglomerate D50" refers to the particle size corresponding to a cumulative volume distribution of 50% of the nanosheet filler agglomerates. The number-average molecular weight Mn of the liquid rubber was determined by gel permeation chromatography and calibrated using polystyrene as a standard.

[0036] (I) Raw materials and testing methods

[0037] The low glass transition temperature solution-polymerized styrene-butadiene rubber used in this embodiment is solution-polymerized styrene-butadiene rubber for tire treads; the polybutadiene rubber is high-cis polybutadiene rubber; the natural rubber is natural rubber for tires; the silica is highly dispersed precipitated silica; the silane coupling agent is a sulfur-containing silane coupling agent; and the carbon black is reinforcing carbon black for tire treads. Reduced graphene oxide is hereinafter referred to as RGO. Organically modified montmorillonite is a layered silicate modified by intercalation with an organic ammonium salt. All nanosheet fillers used are dried before use and then stored in sealed containers.

[0038] Liquid polybutadiene rubber is hereinafter referred to as liquid BR, and liquid styrene-butadiene rubber is hereinafter referred to as liquid SBR. Before use, the liquid rubber should be preheated at 40–50°C to ensure suitable fluidity, but the preheating temperature should not exceed 60°C to reduce oxidation or viscosity changes during pretreatment.

[0039] The D50 of nanosheet filler agglomerates was determined using the following method: For liquid rubber pre-composite nanosheet filler masterbatch, a representative masterbatch sample was taken and diluted with an organic medium capable of dissolving the liquid rubber without reacting with the nanosheet filler. The mixture was stirred at low speed without strong ultrasonic disruption to ensure complete dissolution of the liquid rubber. Subsequently, the agglomerate particle size was determined using a combination of laser particle size analysis and microscopic image analysis. For the comparative example where nanosheet filler powder was directly added, samples were taken from the second-stage masterbatch and, after treatment with the same solvent, the apparent D50 of the nanosheet filler agglomerates in the rubber compound was determined. All samples were subjected to the same sampling, dilution, and analytical conditions to ensure comparability between different samples.

[0040] The Payne effect was evaluated using a dynamic strain scanning method. The difference between the low-strain and high-strain storage moduli was measured at the same temperature and frequency. The modulus difference in Comparative Example 1 was set to 100, and the difference was converted to the Payne index using the following formula:

[0041] Payne index = Modulus difference of the test sample / Modulus difference of comparative example 1 × 100.

[0042] A lower Payne index indicates fewer ineffective networks formed between packing materials, and a greater ease with which the packing network opens under dynamic strain. It should be noted that the Payne index is only used for relative comparisons under the same basic formulation and test conditions.

[0043] tanδ@0℃ and tanδ@60℃ represent the loss factors of the vulcanizate measured at 0℃ and 60℃, respectively. In the same test system of this embodiment, a higher tanδ@0℃ generally indicates better wet grip potential of the tread compound, while a lower tanδ@60℃ generally indicates lower dynamic hysteresis loss and better low rolling resistance potential of the tread compound. Mooney viscosity was determined using ML(1+4) at 100℃.

[0044] The whole tire tests were conducted using 235 / 45R18 passenger car tires of the same specification. Except for differences in the nanosheet filler, liquid rubber, and their addition methods in the tread compound, the carcass, belt layer, sidewall, inner liner, molding process, and vulcanization process were all kept consistent. All performance indicators were indexed with Comparative Example 1 as 100. The wet braking index was converted according to the ratio of the wet braking distance of Comparative Example 1 to that of the test sample; the rolling resistance index was converted according to the ratio of the rolling resistance coefficient of Comparative Example 1 to that of the test sample; the mileage wear index, crack propagation resistance index, extrusion appearance score, and durability index were converted according to the ratios of the test sample results to those of Comparative Example 1. Therefore, except for the Payne index, where a lower value is preferred, all other whole tire performance indices were preferred by higher values.

[0045] This implementation also uses a "comprehensive balance index" to evaluate the comprehensive relationship between wet braking, rolling resistance, wear, and crack propagation resistance. The specific calculation formula is as follows:

[0046] Comprehensive balance index = (wet braking index + rolling resistance index + wear mileage index + crack propagation resistance index) / 4.

[0047] The overall balance index is only used to compare the test results obtained in this embodiment using the same basic formula, the same tire specifications and the same test methods, and is not intended as an absolute performance limit for all tire products.

[0048] (II) Preparation of liquid rubber precomposite nanosheet filler masterbatch

[0049] The basic preparation process of the masterbatch of this invention is as follows: Figure 1 As shown in the diagram, the nanosheet filler was first dried, and the liquid rubber was preheated. Then, the nanosheet filler and liquid rubber were added to a premixing container equipped with a gas purging port. Nitrogen was used to purge the air from the container, and the atmosphere inside the container was monitored using an oxygen content detection device. Premixing began when the oxygen content decreased to no more than 8 vol.%. After premixing, the premix was subjected to high-shear dispersion, ball milling dispersion, or a combination of ball milling dispersion and high-shear dispersion to obtain a liquid rubber pre-composite nanosheet filler masterbatch.

[0050] When using high-shear dispersion, the temperature of the premix should be controlled between 20 and 90°C, preferably between 40 and 70°C, and the dispersion time should be 5 to 120 minutes. When using ball milling dispersion, stainless steel balls with a diameter of 3 to 5 mm can be used as the milling media, and the milling time should be 10 to 300 minutes. When using a combination of ball milling dispersion and high-shear dispersion, it is preferable to first perform ball milling dispersion to open up larger lamellar stacks, and then perform high-shear dispersion to further wet and coat the opened lamellar fillers with liquid rubber. During the dispersion process, a small amount of nitrogen should be continuously introduced or the equipment should be kept sealed to ensure that the oxygen content does not exceed 8 vol.%.

[0051] Figure 1 The specific process flow is illustrated as follows: "Drying of nanosheet fillers—preheating of liquid rubber—low-oxygen premixing—ball milling and / or high-shear dispersion—formation of precomposite masterbatch—addition to the second-stage masterbatch—addition to the vulcanization system in the final refining—obtaining high-silica tread rubber." Figure 1 It is understood that the present invention does not add the nanosheet filler powder and liquid rubber separately during the mixing process, but forms a pre-composite masterbatch with a relatively stable dispersion state before the tread rubber is mixed.

[0052] (III) Basic Formulation of High-Silica Carbon Black Tire Tread Rubber

[0053] The basic formulations used in each embodiment and comparative example are shown in Table 1.

[0054] Table 1. Basic Formulation of High-Silica Carbon Black Tread Rubber

[0055]

[0056] The total amount of rubber components in Table 1 is 100 phr. Unless otherwise stated, the liquid rubber pre-composite nanosheet filler masterbatch in the examples is added as an additional component in addition to the basic formulation in Table 1. The corresponding liquid rubber and nanosheet filler in each comparative example are also added according to the corresponding experimental design to compare the effects of pre-composite treatment, liquid rubber molecular weight, filler to liquid rubber ratio, and addition stage.

[0057] (iv) Phased mixing method

[0058] Except for Comparative Example 6, all other examples and comparative examples employed a staged mixing method, with the specific order of material addition as follows: Figure 2 As shown.

[0059] In the first stage of mastering, 55 phr of solution-polymerized styrene-butadiene rubber, 10 phr of polybutadiene rubber, and 10 phr of natural rubber are added to the internal mixer. After mastication, 75 phr of silica, 6 phr of silane coupling agent, zinc oxide, stearic acid, antioxidant, and protective wax are added. The silica added in the first stage accounts for 60% of the total silica and 60% of the total silane coupling agent. After mixing until the rubber compound temperature reaches 145–155°C, the rubber is discharged, allowing some of the base rubber, silica, and silane coupling agent to form an initial rubber-silica reinforcing network. No liquid rubber pre-composite nanosheet filler masterbatch is added in the first stage of mastering.

[0060] After the first-stage masterbatch is cooled, the second-stage masterbatch is carried out. The first-stage masterbatch, the remainder being 10 phr of polybutadiene rubber, the remainder being 15 phr of natural rubber, the remainder being 50 phr of silica, the remainder being 4 phr of silane coupling agent, 5 phr of carbon black, and 8 phr of TDAE oil are added to the internal mixer. After thorough mixing, liquid rubber pre-composite nanosheet filler masterbatch is added. The discharge temperature of the second-stage masterbatch is controlled at 130–165°C, preferably 145–155°C in this embodiment. This addition method allows the masterbatch to enter the rubber compound based on the initial silica network already formed in the first stage, which helps to reduce the adverse interference of the nanosheet filler on the initial dispersion and silanization process of silica.

[0061] After the masterbatch has cooled in the second stage, it undergoes final refining. During final refining, sulfur, accelerator CZ, and accelerator DPG are added and mixed until the vulcanization system is evenly dispersed before discharge. The discharge temperature during final refining should not exceed 110℃, preferably 95–105℃. No liquid rubber pre-composite nanosheet filler masterbatch is added during the final refining stage.

[0062] like Figure 2 As shown, the main function of the first stage mastering process is to establish the initial rubber-fumed silica network; the second stage mastering process adds the remaining base rubber, remaining fumed silica, remaining silane coupling agent and pre-composite masterbatch, and controls the discharge temperature of the second stage at 130-165℃; in the final stage, sulfur and accelerator are added, and the discharge temperature does not exceed 110℃. Figure 2 It is also clearly shown that the pre-composite masterbatch is added only in the second stage of masterbatch refining, and the timing of this addition constitutes one of the main process differences between Example 5 and Comparative Example 6.

[0063] (v) Examples and Comparative Examples

[0064] Example 1

[0065] RGO and liquid BR with a number average molecular weight of approximately 3500 were added to a premixing container at a mass ratio of 20:80. Nitrogen gas was introduced to replace the air in the container, and premixing was carried out after the oxygen content dropped to below 8 vol.%. The premix was then dispersed under high shear for 45 min under nitrogen protection, with the dispersion temperature controlled at 50–65 °C, to obtain the liquid BR pre-composite RGO masterbatch.

[0066] The tread compound was prepared according to the basic formulation shown in Table 1 and the above-described staged mixing method, and the masterbatch was added in the second stage masterbatch. The amount added was 1.0 phr based on RGO; according to the RGO to liquid BR mass ratio of 20:80, the amount of liquid BR added was 4.0 phr, and the total amount of masterbatch added was 5.0 phr. The D50 of the RGO aggregates in the resulting masterbatch was 14 μm.

[0067] Example 2

[0068] Except for adjusting the mass ratio of RGO to liquid BR to 25:75, the high shear dispersion time to 60 min, and the amount of RGO added to 1.5 phr, the other masterbatch preparation methods and tread rubber mixing methods are the same as in Example 1.

[0069] Based on a mass ratio of 25:75, the amount of liquid BR added in this embodiment is 4.5 phr, and the total amount of masterbatch added is 6.0 phr. The D50 of RGO aggregates in the obtained masterbatch is 10 μm.

[0070] Example 3

[0071] RGO was mixed with liquid SBR with a number average molecular weight of approximately 5000 at a mass ratio of 25:75. Under nitrogen protection and with an oxygen content not exceeding 8 vol.%, the premix was first ball-milled and then subjected to high-shear dispersion. The ball milling process was used to break up larger RGO stacks, while the high-shear process was used to promote further wetting and coating of the RGO sheets by the liquid SBR. After the treatment, a liquid SBR pre-composite RGO masterbatch was obtained.

[0072] The tread compound was prepared according to the basic formulation shown in Table 1 and the above-described staged mixing method. The masterbatch was then added in the second stage of masterbatch mixing. The amount of RGO added was 1.5 phr, the amount of liquid SBR added was 4.5 phr, and the total amount of masterbatch added was 6.0 phr. The D50 of the RGO aggregates in the resulting masterbatch was 9 μm.

[0073] Example 4

[0074] Liquid BR with a number-average molecular weight of approximately 3500 was used as the pre-dispersion carrier, with a RGO to liquid BR mass ratio of 25:75. Ball milling and high-shear dispersion were performed sequentially under nitrogen protection and with an oxygen content not exceeding 8 vol.%. A small amount of silane-based interface stabilizer was added after dispersion. The amount of interface stabilizer added was 1 part by mass, based on a total mass of 100 parts by mass of RGO and liquid BR.

[0075] In this embodiment, the amount of RGO added was 1.5 phr, the amount of liquid BR added was 4.5 phr, the amount of interface stabilizer added was 0.06 phr, and the total amount of precomposite masterbatch added was 6.06 phr. The D50 of the RGO agglomerates in the resulting masterbatch was 8 μm. Subsequently, the tread rubber was prepared according to the above-described staged mixing method, with the precomposite masterbatch added only in the second stage of masterbatch mixing.

[0076] Example 5

[0077] RGO and liquid BR with a number-average molecular weight of approximately 3500 were added to a premixing container at a mass ratio of 20:80. After nitrogen purging to ensure the oxygen content in the container did not exceed 8 vol.%, premixing was performed, followed by ball milling and high-shear dispersion to obtain a liquid BR pre-composite RGO masterbatch. The D50 of the RGO agglomerates in the obtained masterbatch was 7 μm.

[0078] The tread compound was prepared according to the formulation shown in Table 1. No masterbatch was added during the first stage of mastering; during the second stage of mastering, the masterbatch was added after the initial rubber-fumed silica network had been formed, and the discharge temperature was controlled at 145–155°C; the vulcanization system was added during the final stage, and the discharge temperature was controlled at 95–105°C.

[0079] In this embodiment, the amount of RGO added is 1.5 phr, the amount of liquid BR added is 6.0 phr, and the total amount of precomposite masterbatch added is 7.5 phr.

[0080] Example 6

[0081] Organically modified montmorillonite and liquid BR with a number average molecular weight of approximately 3500 were added to a premixed container at a mass ratio of 20:80. The mixture was then dispersed under high shear for 60 minutes under nitrogen protection and with an oxygen content not exceeding 8 vol.% to obtain liquid BR pre-composite organically modified montmorillonite masterbatch.

[0082] The masterbatch was added in the second stage of masterbatch refining, with 2.0 phr of organically modified montmorillonite, 8.0 phr of liquid BR, and a total masterbatch amount of 10.0 phr. The resulting masterbatch had an organically modified montmorillonite agglomerate D50 of 11 μm. The remaining formulation and mixing method were the same as in Example 1.

[0083] The main parameters of Examples 1 to 6 are summarized in Table 2.

[0084] Table 2. Masterbatch composition and preparation parameters of the examples

[0085]

[0086] Note: The total amount of masterbatch in Example 4 includes 0.06 phr of interface stabilizer; the total amount of masterbatch in the other examples is the sum of the amount of nanosheet filler and liquid rubber added.

[0087] Comparative Example 1

[0088] The tread compound was prepared according to the basic formulation shown in Table 1 and the above-described staged mixing method, but without the addition of nanosheet fillers, liquid rubber precomposite masterbatch, or additional liquid rubber. Comparative Example 1 was used as the reference sample, and all relative performance indices were set to 100.

[0089] Comparative Example 2

[0090] The tread compound was prepared according to the formulation of Example 5, but instead of preparing the liquid rubber pre-composite RGO masterbatch in advance, 1.5 phr of RGO powder and 6.0 phr of liquid BR were added to the second-stage masterbatch. The amount of RGO powder and liquid BR added was the same as in Example 5, thereby eliminating the influence caused by the difference in the total amount of raw materials.

[0091] Since RGO is fed directly into the internal mixer in powder form, it is already mixed with silica and the rubber matrix before it comes into full contact with the liquid BR. The apparent D50 of the RGO agglomerates measured in the second-stage masterbatch is 26 μm.

[0092] Comparative Example 3

[0093] Except for the high-shear pre-dispersion of RGO and liquid BR in air atmosphere, the composition of the masterbatch and the preparation method of the tread compound were the same as in Example 5. The mass ratio of RGO to liquid BR was 20:80, the amount of RGO added was 1.5 phr, and the amount of liquid BR added was 6.0 phr. The D50 of the RGO agglomerates in the obtained masterbatch was 18 μm.

[0094] This comparative example is used to evaluate the effect of low oxygen or inert atmosphere on the pre-composite dispersion process.

[0095] Comparative Example 4

[0096] Except for the use of liquid BR with a number-average molecular weight of approximately 25,000, the composition and preparation method of the masterbatch were basically the same as those in the example using liquid BR. The mass ratio of RGO to liquid BR was 20:80, the amount of RGO added was 1.5 phr, and the amount of liquid BR added was 6.0 phr. High-shear dispersion was carried out for 60 min under nitrogen protection. The D50 of RGO agglomerates in the obtained masterbatch was 15 μm.

[0097] This comparative example illustrates that when the molecular weight of liquid rubber is too high, the flow and wetting ability of the liquid rubber decreases, which is not conducive to the full dispersion of the lamellar filler and the subsequent migration and distribution of the masterbatch in the base rubber.

[0098] Comparative Example 5

[0099] A masterbatch was prepared by mixing RGO and liquid BR (with a number average molecular weight of approximately 3500) at a mass ratio of 45:55 and dispersed under high shear for 60 min under nitrogen protection. The amount of RGO added was 1.5 phr. Based on the 45:55 mass ratio, the amount of liquid BR added was 1.83 phr, and the total amount of masterbatch added was approximately 3.33 phr. The D50 of the RGO aggregates in the resulting masterbatch was 17 μm.

[0100] This comparative example illustrates that when the proportion of nanosheet filler in the masterbatch is too high, the amount of liquid rubber corresponding to a unit mass of RGO is insufficient, making it difficult to form a sufficient and continuous wetting and coating state, and the sheet filler is still easy to recombine.

[0101] Comparative Example 6

[0102] Liquid BR pre-composite RGO masterbatch was prepared according to the method in Example 5, with a mass ratio of RGO to liquid BR of 20:80, an RGO addition amount of 1.5 phr, and a liquid BR addition amount of 6.0 phr. However, during the tread rubber compounding, the method of "establishing the initial silica network in the first stage of mastering and adding the masterbatch in the second stage of mastering" was not adopted. Instead, the pre-composite masterbatch and the main silica components were added at once in the first stage of high-temperature mastering.

[0103] In this comparative example, the first-stage mixing temperature reached the high-temperature masterbatch temperature. The pre-composite masterbatch underwent prolonged high-temperature and high-shear conditions, resulting in a rubber compound with an RGO agglomerate D50 of 13 μm. This comparative example illustrates that even if the masterbatch is pre-prepared, improper masterbatch addition can still cause secondary aggregation of already opened lamellar structures.

[0104] The key variables for each pair are summarized in Table 3.

[0105] Table 3 Comparative Design

[0106]

[0107] (vi) Results of tests on dispersion state and dynamic performance

[0108] The aggregate D50, Payne index, tanδ@0℃, tanδ@60℃ and Mooney viscosity test results of each embodiment and comparative example are shown in Table 4.

[0109] Table 4. Results of Dispersion State and Dynamic Performance

[0110]

[0111] As shown in Table 4, the Payne indices of Examples 1-6 ranged from 84 to 92, all lower than the 100 of Comparative Example 1, indicating that pre-dispersing the nanosheet filler in the liquid rubber can reduce its adverse disturbance to the high-precision silica filler network. The tanδ@0℃ values ​​of Examples 1-6 ranged from 0.246 to 0.255, all higher than the 0.238 of Comparative Example 1; the tanδ@60℃ values ​​ranged from 0.090 to 0.094, all lower than the 0.096 of Comparative Example 1, indicating that each example showed a trend of improving wetland gripping potential and reducing dynamic hysteresis loss.

[0112] The Mooney viscosity of Examples 1-6 was 71-73, close to 70 in Comparative Example 1, indicating that the present invention improved the dispersion and dynamic properties of the filler without causing an abnormal increase in the processing viscosity of the rubber compound. Conversely, in Comparative Example 2, when RGO powder and liquid BR were added separately, the agglomerate D50 increased to 26 μm, the Payne index increased to 106, and the Mooney viscosity increased to 76, indicating that directly adding RGO powder not only failed to effectively improve the filler network but also exacerbated local agglomeration and processing fluctuations.

[0113] Example 5 used the same RGO and liquid BR addition amounts as Comparative Example 2. The D50 of Example 5 was 7 μm, only about 26.9% of that of Comparative Example 2; the Payne index decreased from 106 in Comparative Example 2 to 84, a decrease of approximately 20.8%; and tanδ@60℃ decreased from 0.097 to 0.090. This comparison eliminates the influence of different total RGO and liquid BR amounts, indicating that the performance improvement mainly comes from the pre-composite state and its addition method.

[0114] The main difference between Example 5 and Comparative Example 3 lies in the atmosphere conditions during the pre-composite process. The D50 of Example 5 is 7 μm, while that of Comparative Example 3 is 18 μm; the Payne index of Example 5 is 84, while that of Comparative Example 3 is 96, indicating that a low-oxygen or inert atmosphere is beneficial for maintaining the interfacial state between the liquid rubber and the surface of the newly formed sheets during mechanical dispersion and for reducing the need for re-stacking after processing.

[0115] Compared to Comparative Example 4, Example 5 used liquid BR with a number-average molecular weight of approximately 3500, while Comparative Example 4 used liquid BR with a number-average molecular weight of approximately 25000. The D50 of Comparative Example 4 increased to 15 μm, and the Payne index was 94, indicating that when the molecular weight of the liquid rubber is too high, its viscosity and flow characteristics are not conducive to its full penetration into the interlaminar spaces.

[0116] Compared to Comparative Example 5, Example 5 increased the proportion of RGO in the masterbatch to 45%, achieving a D50 of 17 μm, a Payne index of 98, and a Mooney viscosity of 75. These results demonstrate that a higher proportion of lamellar filler in the masterbatch is not always better; when the liquid rubber is relatively insufficient, the lamellar filler is difficult to achieve adequate wetting and coating.

[0117] Compared with Comparative Example 6, both Example 5 and Comparative Example 6 used pre-composite masterbatch, but Comparative Example 6 added the masterbatch all at once in the first stage of high-temperature masterbatch refining. The D50 of Comparative Example 6 was 13 μm and the Payne index was 91, both of which were inferior to those of Example 5. This indicates that limiting the addition of the masterbatch to the second stage of masterbatch refining can reduce the high temperature and high shear process experienced by the masterbatch and is beneficial to maintaining the dispersion state of the pre-composite masterbatch.

[0118] Figure 3 The Payne index and rolling resistance index of Comparative Example 1, Comparative Example 2, and Example 5 are shown. Both indices of Comparative Example 1 are 100; the Payne index of Comparative Example 2 is 106 and the rolling resistance index is 99; the Payne index of Example 5 is 84 and the rolling resistance index is 105. Figure 3 The lower the Payne index, the better; the higher the rolling resistance index, the better. Therefore, Example 5 exhibits both a weaker ineffective filler network and better rolling resistance performance, while Comparative Example 2 shows an increased Payne index and a decreased rolling resistance index. Figure 3 This demonstrates that the direct addition of RGO powder is not equivalent to the addition of liquid rubber precomposite masterbatch.

[0119] (vii) Results of tire performance tests

[0120] The overall tire performance results of each embodiment and comparative example are shown in Table 5.

[0121] Table 5 Overall Tire Performance Results

[0122]

[0123] Based on the data in Table 5, the wet braking index of Examples 1-6 was increased by 4%, 6%, 8%, 7%, 9%, and 5% respectively compared to Comparative Example 1; the rolling resistance index was increased by 2%, 4%, 3%, 4%, 5%, and 3% respectively; the wear mileage index was increased by 3%, 6%, 4%, 8%, 10%, and 6% respectively; and the crack propagation resistance index was increased by 4%, 7%, 5%, 9%, 12%, and 6% respectively. Therefore, Examples 1-6 all achieved improvements in the same direction in the four properties of wet braking, rolling resistance, wear, and crack propagation resistance, proving that the present invention can be implemented and basically consistent comprehensive improvement effects can be obtained under the conditions of different types of liquid rubber, different types of nanosheet fillers, different masterbatch ratios, and different agglomerate particle sizes as defined in this invention.

[0124] Example 3, using liquid SBR as a pre-dispersion carrier, achieved a wet braking index of 108, higher than the 106 of Example 2, indicating that the compatibility between liquid SBR and solution-polymerized styrene-butadiene rubber is beneficial for improving low-temperature dynamic performance. However, the rolling resistance index and wear mileage index of Example 3 were 103 and 104, respectively, slightly lower than those of Examples 4 and 5, which used liquid BR, suggesting that the type of liquid rubber can be selected according to the target performance.

[0125] In Example 4, after adding a small amount of interface stabilizer, the Payne index decreased to 86, and the wear mileage index and crack propagation resistance index reached 108 and 109, respectively, indicating that the interface stabilizer helps maintain the dispersion state and interfacial bonding state of the lamellar filler.

[0126] Example 6 uses organically modified montmorillonite, whose wet braking, rolling resistance, abrasion, and crack propagation resistance indices are 105, 103, 106, and 106, respectively, all higher than those of Comparative Example 1. This result demonstrates that the pre-composite principle of this invention is applicable not only to graphene-based sheet fillers but also to organically modified layered silicates.

[0127] Although Comparative Example 2 achieved a wet braking index of 102, its rolling resistance index, wear mileage index, crack propagation resistance index, extrusion appearance score, and durability index decreased to 99, 97, 96, 98, and 98, respectively. This indicates that directly adding RGO powder may slightly improve a single low-temperature dynamic performance, but it will disrupt the balance between multiple performance aspects.

[0128] After pre-dispersion in air, Comparative Example 3 showed a wet braking index of 104, but its rolling resistance, abrasion, and crack propagation resistance indices were only 101, 102, and 101, respectively, indicating a significantly lower degree of improvement compared to Example 5. Comparative Example 4, using a higher molecular weight liquid BR, showed indices close to those of Comparative Example 1. In Comparative Example 5, the RGO ratio in the masterbatch was too high, resulting in a rolling resistance index of 99 and an extrusion appearance score of 97. Although Comparative Example 6 used a pre-composite masterbatch, its overall improvement was lower than that of Example 5 due to an unsuitable addition stage. These comparative examples demonstrate that low-oxygen treatment, liquid rubber molecular weight, masterbatch ratio, and staged addition method are not isolated factors but rather collectively affect the dispersion, retention, and final performance of the nanosheet filler.

[0129] (viii) Relationship between aggregate particle size and overall performance

[0130] Based on the aforementioned comprehensive balance index calculation formula, the comprehensive balance indices of each embodiment and comparative example are shown in Table 6.

[0131] Table 6. Calculation Results of the Comprehensive Balance Index

[0132]

[0133] The calculation results in Table 6 are all obtained by directly calculating the arithmetic mean of the wet braking index, rolling resistance index, wear mileage index, and crack propagation resistance index from Table 5. For example, the comprehensive balance index of Example 5 is (109 + 105 + 110 + 112) / 4 = 109.00; the comprehensive balance index of Comparative Example 2 is (102 + 99 + 97 + 96) / 4 = 98.50, and the calculation method is consistent.

[0134] Figure 4 The relationship between aggregate D50 and the overall balance index is shown. Figure 4 Circular data points represent examples, and triangular data points represent comparative examples. Comparative Example 1 does not contain nanosheet fillers and therefore does not contain the corresponding agglomerates D50, and is not included. Figure 4 .Depend on Figure 4 It can be seen that the D50 of Example 5 is 7 μm and the comprehensive balance index is 109.00; the D50 of Example 4 is 8 μm and the comprehensive balance index is 107.00; and the D50 of Example 2 is 10 μm and the comprehensive balance index is 105.75. In Comparative Example 2, the D50 increases to 26 μm, and its comprehensive balance index decreases to 98.50. Overall, as the D50 of the aggregates decreases, the comprehensive balance index tends to increase.

[0135] It should be noted that the aggregate D50 is not the sole factor determining performance. For example, the overall balance index of Example 1 and Comparative Example 6 is 103.25, but their masterbatch processing methods and addition stages differ; the overall balance index of Example 3 and Example 6 is 105.00, but their liquid rubber and nanosheet filler types differ. Therefore, Figure 4 This reflects the overall correlation between agglomerate particle size and comprehensive performance. The technical effect of this invention comes from the combined effects of the type and molecular weight of liquid rubber, the ratio of nanosheet filler to liquid rubber, low oxygen dispersion, agglomerate particle size, and the masterbatch addition stage.

[0136] (ix) Comprehensive performance analysis of Example 5

[0137] Figure 5 A radar chart showing the combined performance of Example 5 and Comparative Example 1 is shown. Figure 5 The evaluation includes six dimensions: wet braking index, rolling resistance index, wear mileage index, crack propagation resistance index, extrusion appearance score, and durability index. In Comparative Example 1, all six indices are 100; the corresponding indices for Example 5 are 109, 105, 110, 112, 104, and 106, respectively. Figure 5It can be intuitively seen that Example 5 is no less than Comparative Example 1 in all six evaluation dimensions, and there is no situation where one performance is sacrificed to improve another.

[0138] As shown in Table 4, in Example 5, tanδ@0℃ increased from 0.238 in Comparative Example 1 to 0.255, an increase of approximately 7.1%; tanδ@60℃ decreased from 0.096 to 0.090, a decrease of 6.25%; the Payne index decreased from 100 to 84, a decrease of 16%; and the Mooney viscosity only changed from 70 to 71. These results indicate that Example 5, while maintaining relatively stable processing properties of the rubber compound, reduced the ineffective filler network and improved both low-temperature dynamic properties and high-temperature dynamic hysteresis properties.

[0139] As shown in Table 5, Example 5 exhibits a 9% improvement in wet braking index, a 5% improvement in rolling resistance index, a 10% improvement in wear mileage index, a 12% improvement in crack propagation resistance index, a 4% improvement in extrusion appearance score, and a 6% improvement in durability index. These results are consistent with... Figure 5 The radar profiles shown are consistent, proving that the use of liquid rubber pre-composite RGO masterbatch and its addition in the second-stage masterbatch process can achieve a good balance of multiple properties in the high silica tread system.

[0140] As shown in Examples 1-6, when liquid BR or liquid SBR is used as the pre-dispersion carrier, RGO or organically modified montmorillonite is used as the nanosheet filler, the filler-to-liquid rubber mass ratio is 20:80 to 25:75, the number-average molecular weight of the liquid rubber is approximately 3500 to 5000, and the aggregate D50 is controlled at 7 to 14 μm, the resulting tread rubber exhibits a lower Payne index than the benchmark, a higher tanδ@0℃ than the benchmark, a lower tanδ@60℃ than the benchmark, and improved overall tire performance. Therefore, this invention can be implemented not only with a single raw material or a single process point.

[0141] Comparative Example 2 shows that adding liquid rubber and nanosheet filler separately cannot achieve the same technical effect as the pre-composite masterbatch; Comparative Example 3 shows that a low-oxygen or inert atmosphere helps to obtain smaller agglomerate particle size and a more stable interfacial state; Comparative Example 4 shows that excessively high molecular weight of liquid rubber will weaken its wetting and dispersing effects; Comparative Example 5 shows that an excessively high proportion of nanosheet filler in the masterbatch will lead to insufficient coating of liquid rubber; Comparative Example 6 shows that after the masterbatch is prepared, it is still necessary to select an appropriate addition stage to reduce secondary agglomeration.

[0142] In summary, this invention employs a combined technical route of "liquid rubber pre-composite dispersion under low-oxygen conditions—aggregate particle size control—establishment of an initial silica network in the first stage—addition of pre-composite masterbatch in the second stage—low-temperature final mixing and addition to the vulcanization system." This allows the nanosheet filler to be wetted and coated with liquid rubber before entering the high-silica tread rubber, maintaining good dispersion during subsequent mixing. This reduces ineffective filler networks and improves the overall balance between wet braking, rolling resistance, abrasion, crack propagation resistance, and durability. Those skilled in the art can implement this invention without inventive effort based on the above-mentioned raw material composition, masterbatch ratio, dispersion conditions, feeding sequence, and temperature range.

Claims

1. A method for preparing a high-white carbon black tire tread rubber composition, characterized in that, Includes the following steps: S1. In an atmosphere with an oxygen content not exceeding 8 vol.%, reduced graphene oxide and liquid diene rubber with a number average molecular weight of 1500 to 10000 are premixed at a mass ratio of 20:80 to 25:75, and then ball-milled and dispersed and high-shear dispersed in sequence to obtain a liquid rubber precomposite nanosheet filler masterbatch with a median particle size D50 of reduced graphene oxide agglomerates not exceeding 10 μm. S2. Based on 100 parts by mass of solid rubber component, a portion of solid rubber component, 50-70% of the total amount of silica and 40-70% of the total amount of silane coupling agent are subjected to a first stage of mastering, and the liquid rubber pre-composite nanosheet filler masterbatch is not added in the first stage of mastering to obtain the first masterbatch. S3. The first masterbatch, the remaining solid rubber component, the remaining silica, the remaining silane coupling agent, and the liquid rubber precomposite nanosheet filler masterbatch are subjected to a second stage of masterbatch mixing, so that the amount of the masterbatch added, converted to reduced graphene oxide, is 0.5 to 2.0 parts by mass, and the amount of the masterbatch added, converted to liquid diene rubber, is 3 to 8 parts by mass. The discharge temperature of the second stage masterbatch mixing is 130 to 165°C. S4. The rubber compound obtained from the second stage masterbatch is subjected to final refining with sulfur and accelerator. During the final refining process, the liquid rubber pre-composite nanosheet filler masterbatch is not added again, and the final refining discharge temperature is not higher than 110°C, to obtain the high-white carbon black tire tread rubber composition. The amount of silica added in the high silica tire tread rubber composition is 80-160 parts by weight, and the liquid rubber pre-composite nanosheet filler masterbatch is added only in the second stage masterbatch.

2. The preparation method according to claim 1, characterized in that, The liquid diene rubber is selected from one or more of liquid polybutadiene rubber, liquid styrene-butadiene rubber, carboxylated liquid polybutadiene rubber, and epoxidized liquid polybutadiene rubber; Preferably, the liquid diene rubber is liquid polybutadiene rubber or liquid styrene-butadiene rubber with a number average molecular weight of 3000-5000.

3. The preparation method according to claim 1, characterized in that, In step S1, the ball milling dispersion time is 10–300 min; the high shear dispersion temperature is 20–90 °C, and the high shear dispersion time is 5–120 min; nitrogen is used to replace the air in the ball milling container before ball milling dispersion.

4. The preparation method according to claim 1, characterized in that, The mass ratio of reduced graphene oxide to liquid polybutadiene rubber is 20:80, the number average molecular weight of the liquid polybutadiene rubber is 3000-4000, and the median particle size D50 of the reduced graphene oxide agglomerates in the obtained liquid rubber precomposite nanosheet filler masterbatch is not higher than 8μm.

5. The preparation method according to claim 1, characterized in that, In the high-shear dispersion process of step S1, an interface stabilizer is added. The interface stabilizer is selected from one or more of silane coupling agents, titanate coupling agents, zirconate coupling agents, maleic anhydride grafted oligomers, rosin esters and terpene phenol resins. The amount of interface stabilizer added is 0.1 to 10% of the total mass of the liquid rubber precomposite nanosheet filler masterbatch.

6. The preparation method according to claim 1, characterized in that, Based on 100 parts by weight of solid rubber components, the high-silica tire tread rubber composition comprises: 30-70 parts by weight of solution-polymerized styrene-butadiene rubber, 5-40 parts by weight of polybutadiene rubber, 10-50 parts by weight of natural rubber and / or isoprene rubber, 80-160 parts by weight of silica, 0-20 parts by weight of carbon black, and 4-15 parts by weight of silane coupling agent, and the total amount of the solid rubber components is 100 parts by weight; Preferably, based on 100 parts by weight of solid rubber components, the high-silica tire tread rubber composition comprises 55 parts by weight of solution-polymerized styrene-butadiene rubber, 20 parts by weight of polybutadiene rubber, 25 parts by weight of natural rubber, 125 parts by weight of silica, 5 parts by weight of carbon black, 10 parts by weight of silane coupling agent, 8 parts by weight of TDAE oil, 2.5 parts by weight of zinc oxide, 1.8 parts by weight of stearic acid, 1.8 parts by weight of antioxidant, 1.2 parts by weight of protective wax, 1.7 parts by weight of sulfur, 1.6 parts by weight of accelerator CZ, and 2.0 parts by weight of accelerator DPG; the amount of masterbatch added, converted to reduced graphene oxide, is 1.5 parts by weight, and the amount added, converted to liquid polybutadiene rubber, is 6 parts by weight.

7. A liquid rubber precomposite nanosheet filler masterbatch for use in high-white carbon black tire tread rubber compositions, characterized in that, The masterbatch comprises nanosheet filler and liquid diene rubber, wherein the mass ratio of the nanosheet filler to the liquid diene rubber is 20:80 to 25:75; the number average molecular weight of the liquid diene rubber is 1500 to 10000; the nanosheet filler is pre-dispersed in the liquid diene rubber, and the median particle size D50 of the nanosheet filler agglomerates in the masterbatch is not higher than 10 μm; the nanosheet filler is selected from one or more of reduced graphene oxide, graphene nanosheets, and organic modified layered silicates. Preferably, the nanosheet filler is reduced graphene oxide, the liquid diene rubber is liquid polybutadiene rubber with a number average molecular weight of 3000-4000, the mass ratio of reduced graphene oxide to liquid polybutadiene rubber is 20:80, and the median particle size D50 of the reduced graphene oxide agglomerates is not higher than 8 μm.

8. A high-white carbon black tire tread rubber composition, characterized in that, Based on 100 parts by weight of solid rubber components, the composition includes: 30-70 parts by weight of solution-polymerized styrene-butadiene rubber, 5-40 parts by weight of polybutadiene rubber, 10-50 parts by weight of natural rubber and / or isoprene rubber, 80-160 parts by weight of silica, 0-20 parts by weight of carbon black, 4-15 parts by weight of silane coupling agent, and the liquid rubber pre-composite nanosheet filler masterbatch as described in claim 7; the total amount of the solid rubber components is 100 parts by weight, and the amount of the masterbatch converted to nanosheet filler is 0.5-2.0 parts by weight, and the amount converted to liquid diene rubber is 3-8 parts by weight; the high silica tire tread rubber composition, under the conditions of a test frequency of 10 Hz and a dynamic strain of 0.5%, has a loss factor tanδ of not less than 0.250 at 0℃, a loss factor tanδ of not more than 0.093 at 60℃, and its ML(1+4) Mooney viscosity at 100℃ is not more than 73.

9. A tire, characterized in that, The tire tread comprises at least the high silica tire tread rubber composition of claim 8.

10. The application of the liquid rubber pre-composite nanosheet filler masterbatch according to claim 9 in the preparation of high-white carbon black tire tread rubber composition, characterized in that, First, a portion of the solid rubber component and a portion of the silica are subjected to a first-stage mastering process. Then, the liquid rubber pre-composite nanosheet filler masterbatch is subjected to a second-stage mastering process with the rubber compound obtained from the first-stage mastering process, the remaining silica, and the remaining silane coupling agent. The liquid rubber pre-composite nanosheet filler masterbatch is not added during the first-stage mastering process and the final process.

Citation Information

Patent Citations

  • High-performance tire containing oxidized graphene

    CN105482201A

  • Rubber composition with graphene and liquid rubber

    CN116669863A